Ethnicity in the Caribbean : essays in honor of Harry Hoetink - Oostindie, Gert; Hoetink, H. (Amsterdam academic archive., 2005)
Addresses the workings of ethnicity in the Caribbean where, from the early days of empire through today's post-colonial limbo, it has arguably remained in the centre of public society as well as private life.